Adjustments in the force–frequency relationship during passive and exercise‐induced hyperthermia. Issue 5 (24th September 2014) - Périard, Julien D.; Racinais, Sebastien; Thompson, Martin W.
ABSTRACT Introduction: We examined the extent to which fatiguing cycling exercise in the heat influences contractile function in modulating the force–frequency relationship. Methods: Before (∽37.0°C) and after (∽38.5°C) exercise (ExH) and passive (PaH) hyperthermia, an 8‐s train of stimulation at 10, 20, 50, and 100 Hz (2 s per frequency) and a potentiated twitch were evoked on the relaxed knee extensors using percutaneous stimulation. Results: ExH and PaH produced a decrease in the 20:50 Hz force ratio, indicative of low‐frequency fatigue (P < 0.01). This adjustment was more pronounced after ExH than PaH (P < 0.01). A rightward displacement in the force–frequency relationship occurred after ExH and PaH (P < 0.05) and was exacerbated by ExH (P < 0.05). Peak twitch force also decreased after ExH (P < 0.05). Conclusions: ExH reduces force summation due to development of skeletal muscle fatigue, exacerbating the shift in force–frequency to the right relative to PaH. Muscle Nerve50: 822–829, 2014